A macro-modeling approach for non-linear analysis of multi-story perforated masonry walls with grout and reinforcement concentrated at their pier ends - Palhares, Rodolfo A. (2023)
A current topic of interest in structural engineering is the assessment of the non-linear response of masonry buildings subject to seismic loading. Researchers have proposed several macro-modeling approaches to date, which have been mainly focused on unreinforced masonry. However, there has been little progress on reinforced masonry, particularly partially grouted masonry (PGM), despite its wide use, especially in North America. This is because the numerical simulation of the inelastic behavior of PGM walls is a complex issue, given the interaction between the grouted/reinforced masonry and the ungrouted portions of the system. These two parts have differences in stiffness and the partial grouting also causes non-uniformity of the cross-section. In the study described herein, a relatively simple and practical macro-modeling approach is evaluated for non-linear analysis of PGM walls with reinforcement concentrated at the side ends of piers. For this, previous results of experimental tests and robust two-dimensional finite element models were used as references. Aspects related to the horizontal force‒displacement response, lateral displacement profiles along the height, and damage mechanisms were assessed. A sensitivity analysis of the numerical model was also performed. The results indicate that the macro-model could simulate the global behavior of the experimental walls with low computational cost and good accuracy.